2016
DOI: 10.1002/widm.1181
|View full text |Cite
|
Sign up to set email alerts
|

The lattice‐based approaches for mining association rules: a review

Abstract: The traditional methods for mining association rules (ARs) include two phrases: mining frequent itemsets (FIs)/frequent closed itemsets (FCIs)/frequent maximal itemsets (FMIs) and generating ARs from FIs/FCIs/FMIs. Lattice‐based approaches (LBAs) for mining ARs are new approaches including two phrases: frequent itemset lattice (FIL)/frequent closed itemset lattice (FCIL) building and generating ARs from the lattice. Total mining time of LBAs for mining ARs outperforms the traditional methods for mining ARs. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…Data mining techniques, particularly mining with association rules, may help to identify the parameters related to agroecological production (de Barros et al, 2013). The identification of association rules is a data mining technique that aims to identify specific data patterns in large databases, which can be interpreted to obtain specific knowledge regarding the problem under consideration (Le and Vo, 2016).…”
Section: Arnmentioning
confidence: 99%
See 1 more Smart Citation
“…Data mining techniques, particularly mining with association rules, may help to identify the parameters related to agroecological production (de Barros et al, 2013). The identification of association rules is a data mining technique that aims to identify specific data patterns in large databases, which can be interpreted to obtain specific knowledge regarding the problem under consideration (Le and Vo, 2016).…”
Section: Arnmentioning
confidence: 99%
“…Association rules are used as data mining techniques to identify specific patterns in the data found in large databases, where the interpretation of these patterns can allow the extraction of specific knowledge about the problem under consideration (Le and Vo, 2016;Kuo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In [20], Tran et al proposed the GEN_ITEMSETS algorithm to generate all itemsets from a lattice of FCIs and generators without repetitions. More recently, Le and Vo [12] proposed an N-list-based algorithm for mining FCIs, named NAFCP. The experimental evaluation of this work has shown that NAFCP outperforms state-of-art FCI mining algorithms in terms of runtime and memory usage in most cases.…”
Section: Mining Frequent (Closed) Itemsetsmentioning
confidence: 99%
“…The authors of Charm proposed the CharmL algorithm [8], which builds the lattice of FCIs. Formal concept (i.e., lattice of FCIs) analysis is also another way of mining FIs as well as ARs [6,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted a lot of research and become an ideal topic in recent years. There are many approaches, which were summarized in [13], to mine such patterns including META [12], MERIT [14], MEI [15], and EIFDD [16]. Several related problems of mining erasable closed itemsets [17], top-rank-k erasable itemsets [18], erasable itemsets with constraints [19], and weighted erasable itemsets [20,21] have also been developed.…”
Section: Introductionmentioning
confidence: 99%